Human-centred computer architecture: redesigning the mobile datastore and sharing interface - Reitmaier, Thomas Oliver (Department of Computer Science, 2019)
This dissertation develops a material perspective on Information & Communication Technologies and combines this perspective with a Research through Design approach to interrogate current and develop new mobile sharing interfaces and datastores. through this approach I open up a line of inquiry that connects a material perspective of information with everyday sharing and communication practices as well as with the mobile and cloud architectures that increasingly mediate such practices. With this perspective, I uncover a shifting emphasis of how data is stored on mobile devices and how this data is made available to apps through sharing interfaces that prevent apps from obtaining a proper handle of data to support fundamentally human acts of sharing such as giving. I take these insights to articulate a much wider research agenda to implicate, beyond the sharing interface, the app model and mobile datastore, data exchange protocols, and the Cloud. I formalise the approach I take to bring technically and socially complex, multi-dimensional and changing ideas into correspondence and to openly document this process. I consider the history of the File abstraction and the fundamental grammars of action this abstraction supports (e.g. move, copy, & delete) and the mediating role this abstraction – and its graphical representation – plays in binding together the concerns of system architects, programmers, and users. Finding inspiration in the 30 year history of the file, I look beyond the Desktop to contemporary realms of computing on the mobile and in the Cloud to develop implications for reinvigorated file abstractions, representations, and grammars of actions. First and foremost, these need to have a social perspective on files. To develop and hone such a social perspective, and challenge the assumption that mobile phones are telephones – implying interaction at a distance – I give an interwoven account of the theoretical and practical work I undertook to derive and design a grammar of action – showing – tailored to co-present and co-located interactions. By documenting the process of developing prototypes that explore this design space, and returning to the material perspective I developed earlier, I explore how the grammars of show and gift are incongruent with the specific ways in which information is passed through the mobile’s sharing interface. This insight led me to prototype a mobile datastore – My Stuff – and design new file abstractions that foreground the social nature of the stuff we store and share on our mobiles. I study how that stuff is handled and shared in the Cloud by developing, documenting, and interrogating a cloud service to facilitate sharing, and implement grammars of actions to support and better align with human communication and sharing acts. I conclude with an outlook on the powerful generative metaphor of casting mobile media files as digital possessions to support and develop human-centred computer architecture that give people better awareness and control over the stuff that matters to them.